Strategic Hiring Behavior in Empirical Matching Functions - René Fahr; Uwe Sunde (Institute for the Study of Labor (IZA), 2001)
This paper makes two contributions to the empirical matching literature. First, a recent study by Anderson and Burgess (2000) testing for endogenous competition among job seekers in a matching frame-work, is replicated with a richer and more accurate data set for Germany. Their results are confirmed and found to be surprisingly robust. Second, the matching framework is augmented by endogenous strategic hiring behavior on the side of vacancyposting firms. Neglecting job competition, the relevance of strategic hiring is shown using the same empirical strategy. At the same time, the test is shown to be invalid if both types of endogenous behavior are present
Keywords: J64; J41; 330; Matching models; job search; vacancies; unemployment; job competition; strategic hiring; Arbeitsnachfrage; Strategie; Arbeitsuche; Wettbewerb; Arbeitsmarkt; Matching; Schätzung; Deutschland